Rotation induced by non-uniform gas–solid phase reactions of a non-spherical particle. (1st November 2022) - Zhou, Shengyu; Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Dai, Zhenghua; Liu, Haifeng
Highlights: The particle rotation induced by gas–solid phase reactions is revealed; The non-uniform gas–solid phase reaction directly results to the rotation of non-spherical particle; The rotation characteristics of coal particle during combustion are discussed. Abstract: Particle rotation plays an important role in gas–solid flow. The particle rotation induced by gas–solid phase reaction is investigated in this work. The non-uniform gas–solid phase reaction direct results to the rotation of a non-spherical particle. Based on the random distribution of active sites, the combustion of non-spherical particles is numerical investigated. According to the numerical results of chemical reaction rate on the particle surface, the net force and the rotation frequency of non-spherical particle were obtained by post-processing. The bearing force and rotation of cubic particles caused by gas–solid chemical reactions are systematically numerically studied. The rotational frequency is basically consistent with the experimental results in the reference. For coal char particles with an active area ratio of 0.8, the rotational frequency can reach 1000 Hz at side length of 60 μm. The effects of active area ratio, ambient gas temperature and particle size on the induced thrust and the rotational frequency of coal char particles are analyzed. The unbalanced force on the particle surface increase with the reaction rates. The rotation velocity increases with the decrease of particle size. And it increases with the increase of ambient temperature..